The science fair is freaky! - Chabert, Jack; Ricks, Sam; Branches (Scholastic Inc.) (New York : Branches/Scholastic Inc., 2016)
For the first time in years Eerie Elementary is planning a science fair, which may not be a good idea in a school which is alive and out to get the students--but when Sam and his friends find a book of experiments that contains all of Orson Eerie's notes, it may turn out to be the key they need to finally understand the mad scientist.
490
Keywords: Science fairs -- Juvenile fiction; Science projects -- Juvenile fiction; Elementary schools -- Juvenile fiction; Best friends -- Juvenile fiction; Scientists -- Juvenile fiction; Horror tales; Science fairs -- Fiction; Science projects -- Fiction; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Scientists -- Fiction; Horror stories; Horror fiction